On coho salmon Oncorhynchus kisutch from Iturup Island - A. N. Elnikov; O. V. Zelennikov (Известия ТИНРО, 2023)
Results of biological analysis are presented for 162 specimens of coho salmon caught at the coast and in the rivers of Iturup Island (southern Kuril Islands) during their spawning migration in August-October, 2021. Almost all females and males close to puberty in the current year spent one year in the sea and were aged 1.1+ (66.7 %) and 2.1+ (30.0 %). The fish that spent two years in the sea were single – 1 specimen aged 1.2+ and 3 specimens aged 2.2+ (2.5 %). Taking into account the age of puberty and the body weight (2.63 kg for females and 2.44 kg for males, on average) the spawners reproduction in short streams is assumed. The high value of the gonad-somatic index (up to 20–22 % for some females) is other evidence that all these fish cannot run to other spawning areas but at least a part of them should spawn in the water bodies of Iturup Island. Indeed, some coho salmon were captured directly in the rivers. Beside the spawning fish, two actively feeding coho females aged 0.0+ (0.55 kg) and 1.0+ (1.11 kg) were caught with fixed nets.